2020
DOI: 10.1093/gji/ggaa404
|View full text |Cite
|
Sign up to set email alerts
|

Modelling high-frequency seismograms at ocean bottom seismometers: effects of heterogeneous structures on source parameter estimation for small offshore earthquakes and shallow low-frequency tremors

Abstract: Summary The source characteristics of offshore seismic events, especially regular (or fast) and slow earthquakes, can provide key information on their source physics and frictional conditions at the plate boundary. Due to strong three-dimensional heterogeneities in offshore regions, such as those relating to seawater, accretionary prism, and small-scale velocity heterogeneity, conventional methods using a one-dimensional Earth model may misestimate source parameters such as the duration and radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 102 publications
1
42
0
Order By: Relevance
“…Such a high‐resolution S‐wave velocity structure of seafloor sediments will enhance seismic waveform modeling of body waves at high frequencies, at generally greater than 0.1 Hz, for studying the deeper structures (e.g., Harmon et al., 2007) or seismic source properties beneath the ocean (e.g., Nakano et al., 2015; Takemura et al., 2020). This is because the velocity contrast across the acoustic basement strongly affects the waveform amplitude.…”
Section: Potential Of Obs Array For Investigating 3‐d Sedimentary Str...mentioning
confidence: 99%
See 1 more Smart Citation
“…Such a high‐resolution S‐wave velocity structure of seafloor sediments will enhance seismic waveform modeling of body waves at high frequencies, at generally greater than 0.1 Hz, for studying the deeper structures (e.g., Harmon et al., 2007) or seismic source properties beneath the ocean (e.g., Nakano et al., 2015; Takemura et al., 2020). This is because the velocity contrast across the acoustic basement strongly affects the waveform amplitude.…”
Section: Potential Of Obs Array For Investigating 3‐d Sedimentary Str...mentioning
confidence: 99%
“…Ocean bottom seismometer (OBS) networks of both temporary and permanent deployment have been recently developed along subduction zones (e.g., Cascadia Initiative: Toomey et al., 2014; DONET: Kaneda et al., 2015; S‐net: Kanazawa et al., 2016). High‐frequency waveform data from OBSs, most of which were obtained at frequencies higher than 0.1 Hz, can be used in receiver function analysis for evaluating shallow subduction structures (e.g., Akuhara & Mochizuki, 2015; Reeves et al., 2015) or waveform modeling to determine seismic source properties (e.g., Nakano et al., 2015; Takemura et al., 2020). Such studies help us to better understand the lithology, deformation, and earthquake processes of subduction zones.…”
Section: Introductionmentioning
confidence: 99%
“…We first determined tremor source locations by the envelope correlation method (Ide, 2010;Obara, 2002). We used the daily average of these locations (Figure S1) for energy estimations because of their large scatter, which may be due to strong heterogeneities in velocity structures in the accretionary prism (Takemura et al, 2020). We next computed the energy rate waveforms at the source from three-component seismograms that were band-pass filtered between 2 and 8 Hz and corrected for the site amplification factors given by Yabe et al (2021).…”
Section: Estimation Of Tremor Size Distributionmentioning
confidence: 99%
“…The seismic energy rate was then calculated by dividing the estimated Ei by the duration of the tremors defined above. Takemura et al (2020) showed that the estimated durations of shallow tremors described above could be overestimated. An accretionary prism with a low seismic velocity is present in the Nankai Trough.…”
Section: Slow Earthquake Catalogs and Seismic Datamentioning
confidence: 92%